A new continuous sliding mode control approach with actuator saturation for control of 2-DOF helicopter system. (March 2018) - Sadala, S.P.; Patre, B.M.
Abstract: The 2-degree of freedom (DOF) helicopter system is a typical higher-order, multi-variable, nonlinear and strong coupled control system. The helicopter dynamics also includes parametric uncertainties and is subject to unknown external disturbances. Such complicated system requires designing a sophisticated control algorithm that can handle these difficulties. This paper presents a new robust control algorithm which is a combination of two continuous control techniques, composite nonlinear feedback (CNF) and super-twisting control (STC) methods. In the existing integral sliding mode (ISM) based CNF control law, the discontinuous term exhibits chattering which is not desirable for many practical applications. As the continuity of well known STC reduces chattering in the system, the proposed strategy is beneficial over the current ISM based CNF control law which has a discontinuous term. Two controllers with integral sliding surface are designed to control the position of the pitch and the yaw angles of the 2- DOF helicopter. The adequacy of this specific combination has been exhibited through general analysis, simulation and experimental results of 2-DOF helicopter setup. The acquired results demonstrate the good execution of the proposed controller regarding stabilization, following reference input without overshoot against actuator saturation and robustness concerning to the limited matched disturbances. Highlights: A new robust continuous sliding mode control approach with actuator saturation is presented. ISM based CNF control law is modified for higher order, MIMO nonlinear coupled systems with the matched disturbances. The proposed control law is effective as advantages of CNF, STC and integral sliding surface are incorporated in it. The proposed control law is demonstrated via simulation and experimental results on a 2-DOF helicopter setup.